Association of Elevated Posterior Tibial Slope With Revision Anterior Cruciate Ligament Graft Failure in a Matched Cohort Analysis. Issue 1 (January 2023) - Duerr, Robert A.; Ormseth, Benjamin; DiBartola, Alex; Geers, Katie; Kaeding, Christopher C.; Siston, Robert; Flanigan, David C.; Magnussen, Robert A.
Background: Elevated posterior tibial slope (PTS) has been identified as an important risk factor in anterior cruciate ligament (ACL) injuries and ACL graft failures. The cutoff value to recommend treatment with slope-reducing osteotomy remains unclear and is based on expert opinion and small case series. Purpose: (1) To determine whether there is a difference in PTS shown on lateral knee radiographs and magnetic resonance imaging (MRI) scans in a group of patients who experienced revision ACL graft failure versus a control group of patients who underwent successful revision ACL reconstruction, (2) to identify cutoff values of PTS measurements that predict risk of revision ACL graft failure, and (3) to examine whether there is a correlation between radiographic and MRI measurements of PTS. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 38 patients who experienced revision ACL graft failure were identified from a revision ACL database. These patients were matched 1:1 by age, sex, and graft type to a group of 38 control patients who underwent revision ACL reconstruction with no evidence of graft failure at a minimum 2 years of follow-up. Medial and lateral PTS were measured by lateral knee radiographs and MRI scans of the affected limb. Demographics, surgical characteristics, and PTS were compared between the groups. The optimal cutoff values of medial and lateral PTS per radiographs and MRI scans for predicting increased risk of revision ACL graft failure were determined by receiver operating characteristic curves. Conditional multivariable logistic regression was used to assess the relative contribution of PTS cutoff values as a predictor of revision graft failure. Results: The mean PTS values in the failure group were significantly higher than those in the control group on radiographs (medial, 13.2°± 2.9° vs 10.3°± 2.9°; P < .001; lateral, 12.9°± 3.0° vs 9.8°± 2.8°; P < .001) and MRI scans (medial, 7.2°± 3.1° vs 4.8°± 2.9°; P < .001; lateral, 8.4 ± 3.1° vs 5.9 ± 3.0°; P < .001). A radiographic medial PTS ≥14° had the highest increased risk of revision ACL graft failure with sensitivity equal to 50% and specificity to 92.1% (odds ratio, 18.71; 95% CI, 2.0-174.9; P = .01). Conclusion: Elevated PTS was a significant risk factor for revision ACL graft failure. Patients with radiographic medial PTS ≥14° had 18.7-times increased risk of revision ACL failure.